Hubungan antara Kepercayaan Diri dengan Komunikasi Interpersonal Siswa - Damayanti, Natasya Meilina; Kholili, Ma'rifatin Indah; Dewantoro, Adi (Universitas Sebelas Maret, 2023)
The aims of this research are: Describe the level of self-confidence, interpersonal communication skills and analyze the relationship of self- confidence with the interpersonal communication of second grade students of SMA Negeri 1 Karanganyar. This research is quantitative research with correlational methods. The population is second grade students of SMA Negeri 1 Karanganyar with a total population of 431 people. The sampling technique is simple random sampling. Sampling was carried out using the Slovin formula which was then obtained from a research sample of 207 people with details of 17-18 people per class. The research instruments are self-confidence scale and interpersonal communication skills scale. The answer choices use the likert scale with 4 answer choices and analyzed using Product Moment Correlation in SPSS. The results of study obtained that students with low communication skills were 17%, medium at 63%, and high at 20%. While the coefficient value of 0.397 with a sig value of 0.000, which means if it is 0.000 < 0.05 then the confidence variable and the interpersonal communication variable have a relationship. The two have a positive relationship, it means when the level of self-confidence is high, the student's interpersonal communication are also high.